Digestibility of Coconut Coir Fiber Fermented by Buffalo Rumen Fluid Microbes in Vitro - Dewi, Wuryani Kusuma; Nuswantara, Limbang Kustiawan; Surono, Surono (Jurnal Agripet, 2025)
This study aimed to examine the digestibility of fiber, including crude fiber, neutral detergent fiber (NDF), and acid detergent fiber (ADF) digestibility of coconut husk fermented using selected buffalo rumen microbes with varying percentages of inoculum and fermentation periods. The study utilized a completely randomized design (CRD) with a factorial pattern (33) and 3 replications. The first factor was the percentage of inoculum (0%, 2.5%, and 5% mL of inoculum per gram of dry matter of coconut husk), and the second factor was the fermentation period (0, 7, and 14 days). The collected data were analyzed using analysis of variance (ANOVA) and, where applicable, Duncans multiple range test. The results indicated that there was no significant interaction (P0.05) between the different percentages of buffalo rumen fluid as inoculum and the varying fermentation periods on crude fiber and ADF digestibility of coconut husk. However, the percentage of buffalo rumen fluid as inoculum had a significant effect (P0.05) on crude fiber and ADF digestibility, and the fermentation period also significantly influenced (P0.05) ADF digestibility. An interaction between the percentage of buffalo rumen fluid and fermentation period had a significant effect (P0.05) on NDF digestibility. The findings concluded that the percentage of buffalo rumen fluid as inoculum and the fermentation period did not increase crude fiber and ADF digestibility; however, the interaction between 2.5% buffalo rumen fluid inoculum and a 14-day fermentation period resulted in improved NDF digestibility of coconut husk.